Crystallization and Investigation of the Structural and Optical Properties of Ce3+-Doped Y3−xCaxAl5−ySiyO12 Single Crystalline Film Phosphors - Vitalii Gorbenko; Tetiana Zorenko; Sandra Witkiewicz-Łukaszek; Anna Shakhno; Andres Osvet; Miroslaw Batentschuk; Aleksandr Fedorov; Yuriy Zorenko (Crystals, 2021)
This work is devoted to the crystallization and investigation of the optical properties of single crystalline films (SCFs) of Ce3+-doped Y3−xCaxAl5−ySiyO12 garnet, where the content of Ca2+ and Si4+ cations varied in the x = 0.13–0.52 and y = 0.065–0.5 ranges, respectively. The SCF samples were grown using the liquid phase epitaxy technique onto Y3Al5O12 substrates from the melt solution with equimolar Ca and Si content using PbO-B2O3 flux. However, the Ca and Si concentration in Y3−xCax Al5−ySiyO12:Ce SCFs is not equal: the Ca2+ content was systematically larger than that of Si4+, and the Ca2+ excess is compensated for by the Ce4+ ion formation. The absorption, scintillation, and luminescent properties of Y3−xCaxAl5−ySiyO12:Ce SCFs with different Ca/Si concentrations were investigated and compared with the sample of YAG:Ce SCF. Due to the creation of Ce4+ ions, the as-grown Y3−xCaxAl5−ySiyO12:Ce SCFs show relatively low light yield (LY) under α–particle excitation but a fast scintillation response with a decay time in the ns range. After SCF annealing in the reducing (N2 + H2) atmosphere at T > 1000 °C, the recharging of Ce4+→Ce3+ ions occurs. Furthermore, the samples annealed at 1300 °C SCF possess an LY of about 40% in comparison with the reference YAG:Ce SCF and scintillation decay kinetics much closer to that of the SCF counterpart. Due to Ca2+ and Si4+ alloying, the Ce3+ emission spectra in Y3−xCaxAl5−ySiyO12 SCFs are extended to the red range in comparison with the spectra of YAG:Ce SCF. Such an extension is caused by the Ce3+ multicenter formation at the substitutions of both Y3+ and Ca2+ dodecahedral positions in the hosts of these mixed garnets.